Foodborne Pathogen Assessment in Raw Milk Cheeses - Nicola Costanzo; Carlotta Ceniti; Adriano Santoro; Maria Teresa Clausi; Francesco Casalinuovo (International Journal of Food Science)
General hygienic parameters and selected foodborne pathogens in raw milk cheeses at the retail level were evaluated. A total of 245 raw milk cheese samples were analysed for total bacterial count, Enterobacteriaceae, E. coli, Salmonella spp., Listeria monocytogenes, coagulase-positive Staphylococci, and staphylococcal enterotoxin. Results showed only 3 samples that were not compliant with European rules on staphylococcal enterotoxin, but coagulase-positive Staphylococci were evidenced in all samples tested. Salmonella spp. and Listeria monocytogenes were never detected whereas E. coli was evidenced in 20 samples. Results suggest a need for improvement of good manufacturing practice and milking operation.